EKSISTENSI UMAT BUDHA DI KOTA BLANG PIDIE: TELAAH HUBUNGAN SOSIAL KEAGAMAAN - Nora Afrianja (Abrahamic Religions: Jurnal Studi Agama-Agama, 2022)
Aceh is one of the provinces that adhere to various religions. Aceh or commonly dubbed as 'Beumo Seuramo Meukah' is predominantly Muslim, of course Aceh is based on Islamic Shari'a and also has a special Qanun formulated in accordance with Islam itself. The various adherents of religious communities also do not rule out the possibility of conflicts arising from excessive fanaticism so that the emergence of a sense of intolerance in every religious community. The ummah is an inseparable part of religion, the existence of the ummah is the most important thing in religion or also commonly referred to as followers. Religion does not exist without the adherents of that religion, there are those who lead the event, there are those who prepare the place and tools for the ceremony, and at the same time they become participants. The existence of the people is very influential on the religion itself, the achievement of that religion and the social relations that have a big influence on the religion itself. Relations among religious people based on tolerance, mutual understanding, mutual respect, respect for equality in the experience of religious teachings and cooperation in social life, or what is commonly termed 'religious harmony'. The process of this research through descriptive-qualitative, among others, are: observation, interviews and literature review that reads several book references that are related to this research. The results of this study indicate that there are several dimensions of the socio-religious life of Buddhists in Blang Pidie City, including: the religious dimension, the dimension of social interaction and the dimension of attitude, some of these dimensions can cause factors that affect the socio-religious life of the Buddhist community in Blang Pidie City. Social interactions that are not well established can also have an impact on every individual in society in everyday life.